Epidemiological profile and risk factors predictors of COVID-19 in southern Brazil (Research, Society and Development, 2021)
Detecting factors associated with risk or protection for COVID-19 is essential to determine possible public prevention policies related to epidemic conditions. The objective of this study is to analyze the epidemiological profile, as well as to analyze the predictive variables of risk and protection for COVID-19, in the southern region of Brazil. An epidemiological study was carried out, based on a 34-week time series and based on the database on COVID-19 from the -19 from the State Secretariats of Health of Rio Grande do Sul, Santa Catarina and Paraná, Brazil. Calculations of prevalence, incidence, frequency tables, chi-square test, odds ratio and binary regression were used using the SPSS statistical program, v.22. The results of this study indicated that the variables state, sex, age and comorbidity predict the condition of infected people to recover, die, manifest symptoms or be hospitalized due to COVID-19.